Дослідження актуальності трафаретного друку - Трусова, Т. (My University, 2020)
Дослідження актуальності трафаретного друку. Screen printing is used to print single-color and multi-color illustrated products for various purposes. Now on the world market, you can see a significant number of products printed by screen printing: business cards, postcards, packaging, labels, stickers, various promotional souvenir products
Keywords: трафаретний друк